Study on the capacity of medicinal intake and release of the polymeric polyurethane and biological parts of pomegranate fruit nanocomposite - Peyman Mohammadzadeh Jahani; Hooshang Hamidian; Ali Behrad Vakylabad; Maedeh Jafari; Samieh Fozuni; Hanieh Sharafinejad (مواد نوین, 2022)
Introduction: Nanocomposites are used in biological research due to their unique properties like non-toxicity and biocompatibility. In this study, a new nanocomposite was prepared using polyurethane polymer, and the meaty middle part of the pomegranate which infixed with nano-silver particles. Method: The nanocomposites containing polyurethane polymer, meaty shortcut part of pomegranate fruit, silver nanoparticles, and ciprofloxacin (drug) were chemically synthesized. SEM photomicrographs confirmed the presence of spherically dispersed silver nanoparticles. The combination of polyurethane with different weight percentages of pomegranate broiler was studied.Results: The best performance for drug uptake (4.85 g/g) and release (0.45 g/l) was obtained using a combination of polyurethane polymer with 5 g of pomegranate middling meat, and 1 g of silver nanoparticles (NC3). SEM analysis determined the morphology and dispersion of nanoparticles. FTIR and XRD analysis showed specific peaks (at 2-thetas of 27.01, 38.103, 44.374, 64.541) of silver indicating successful synthesis of the nanocomposites. By studying the particle size distribution (PSD) of silver nanoparticles, SEM image analyses and XRD crystalline size analysis showed that there was a very good match between these two PSDs. This indicates the high dispersion of nanoparticles in composite paste without agglomeration, which was the main reason for the high efficiency of nanocomposite in drug adsorption and dispersion in an aqueous environment. The soluble calibration curve with specified percentages of this drug was used to measure the quantitative dissolution of ciprofloxacin. The maximum wavelength of ciprofloxacin absorption was 270 nm in UV-Vis spectrophotometry analysis.